Impacto do ensino do pensamento computacional sobre habilidades do século XXI: uma revisão sistemática da literatura - Santana, Beatriz Silva de (2021)
The promotion of computational thinking within the school environment has been encouraged and researched around the world, as it is known as a desirable capacity for everyone and its development is pointed out as a possibility to enhance several human skills. Conversely, skills considered fundamental for the 21st century are still not as well developed within the school environment. Taking into account that computational thinking is considered a possible driver of these skills, this research sought to gather and summarize the primary studies that promoted this ability and analyzed the development of 21st century skills. We used the methodology of systematic literature review and, through it, we identified 39 primary studies that met the objective of this research. As a result of the analysis carried out, we found evidence of positive results from the promotion of computational thinking in relation to the development of the following 21st century skills: learning to earn, collaboration, communication, creativity, social skills, problem solving, ICT literacy, innovation ,critical thinking and teamwork. In addition, we promote a discussion on the quality of the available evidence and present ways to increase the quality and reliability of the data available in studies in the area. We conclude that, according to the available studies, promoting computational thinking in K- 12 schools is beneficial in relation to the development of some of the 21st century skills, however, more research needs to be carried out so that we can have results with a higher quality content and understand what scenarios and methods can benefit from this promotion.